Functional significance of SRJ domain mutations in CITED2 - Chen, C; Bentham, J; Cosgrove, C; Braganca, J; Cuenda, A; Bamforth, S; Schneider, J; Watkins, H; Keavney, B; Davies, B; Bhattacharya, S (Public Library of Science, 2012)
CITED2 is a transcriptional co-activator with 3 conserved domains shared with other CITED family members and a unique Serine-Glycine Rich Junction (SRJ) that is highly conserved in placental mammals. Loss of Cited2 in mice results in cardiac and aortic arch malformations, adrenal agenesis, neural tube and placental defects, and partially penetrant defects in left-right patterning. By screening 1126 sporadic congenital heart disease (CHD) cases and 1227 controls, we identified 19 variants, including 5 unique non-synonymous sequence variations (N62S, R92G, T166N, G180-A187del and A187T) in patients. Many of the CHD-specific variants identified in this and previous studies cluster in the SRJ domain. Transient transfection experiments show that T166N mutation impairs TFAP2 co-activation function and ES cell proliferation. We find that CITED2 is phosphorylated by MAPK1 in vitro at T166, and that MAPK1 activation enhances the coactivation function of CITED2 but not of CITED2-T166N. In order to investigate the functional significance in vivo, we generated a T166N mutation of mouse Cited2. We also used PhiC31 integrase-mediated cassette exchange to generate a Cited2 knock-in allele replacing the mouse Cited2 coding sequence with human CITED2 and with a mutant form deleting the entire SRJ domain. Mouse embryos expressing only CITED2-T166N or CITED2-SRJ-deleted alleles surprisingly show no morphological abnormalities, and mice are viable and fertile. These results indicate that the SRJ domain is dispensable for these functions of CITED2 in mice and that mutations clustering in the SRJ region are unlikely to be the sole cause of the malformations observed in patients with sporadic CHD. Our results also suggest that coding sequence mutations observed in case-control studies need validation using in vivo models and that predictions based on structural conservation and in vitro functional assays, or even in vivo global loss of function models, may be insufficient.